Acidic pH Is Required for the Multilamellar Assembly of Skin Barrier Lipids In Vitro - Nováčková, Anna; Sagrafena, Irene; Pullmannová, Petra; Paraskevopoulos, Georgios; Dwivedi, Anupma; Mazumder, Anisha; Růžičková, Karolína; Slepička, Petr; Zbytovská, Jarmila; Vávrová, Kateřina (The Journal of investigative dermatology, 2021)
Lipid membrane remodeling belongs to the most fundamental processes in the body. The skin barrier lipids, which are ceramide dominant and highly rigid, must attain an unusual multilamellar nanostructure with long periodicity to restrict water loss and prevent the entry of potentially harmful environmental factors. Our data suggest that the skin acid mantle, apart from regulating enzyme activities and keeping away pathogens, may also be a prerequisite for the multilamellar assembly of the skin barrier lipids. Atomic force microscopy on monolayers composed of synthetic or human stratum corneum lipids showed multilayer formation (approximately 10-nm step height) in an acidic but not in a neutral environment. X-ray diffraction, Fourier transform infrared spectroscopy, and permeability studies showed markedly altered lipid nanostructure and increased water loss at neutral pH compared with that at acidic pH. These findings are consistent with the data on the altered organization of skin lipids and increased transepidermal water loss under conditions such as inadequate skin acidification, for example, in neonates, the elderly, and patients with atopic dermatitis.
Keywords: ceramidy; mikroskopie atomárních sil; mastné kyseliny; epidermis; cholesterol; Female; Epidermis; Water Loss, Insensible; novorozenec; Age Factors; Dermatitis, Atopic; Hydrogen-Ion Concentration; Fatty Acids; ženské pohlaví; perspiratio insensibilis; Ceramides; věkové faktory; Fatty Acids, Nonesterified; lidé; Infant, Newborn; Spectroscopy, Fourier Transform Infrared; atopická dermatitida; Cholesterol; spektroskopie infračervená s Fourierovou transformací; X-Ray Diffraction; difrakce rentgenového záření; Aged; kyseliny mastné neesterifikované; permeabilita; Permeability; Microscopy, Atomic Force; senioři; koncentrace vodíkových iontů; Humans